2020
DOI: 10.1039/d0cp03831h
|View full text |Cite
|
Sign up to set email alerts
|

The InSe/SiH type-II van der Waals heterostructure as a promising water splitting photocatalyst: a first-principles study

Abstract: Photocatalytic water splitting for hydrogen production has attracted increasing research attention in recent years, great efforts have been made in order to find the ideal photocatalyst. In this work, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…These values are in good agreement with the previous reports. 26,29,[45][46][47] The band structures of MoS 2 and SiH monolayers obtained by the PBE and HSE functionals are depicted in Fig. 1(b), (c), (f) and (g).…”
Section: Resultsmentioning
confidence: 99%
“…These values are in good agreement with the previous reports. 26,29,[45][46][47] The band structures of MoS 2 and SiH monolayers obtained by the PBE and HSE functionals are depicted in Fig. 1(b), (c), (f) and (g).…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Consequently, when a type II heterostructure is formed, the built-in electric field increases the spatial separation of charge carriers in the two separate 2D materials, increasing the photocatalytic quantum efficiency. 53,54 To boost the photocatalytic performance of a 2D SiH layer, it was proven that SiH-based vdW type II heterostructures, such as SiH/TiO 2 , 55 GaAs/SiH, 56 InSe/SiH 57 and PtSe 2 /SiH, 15 which have been theoretically predicted to be excellent photocatalytic materials, can split water into H 2 under solar irradiation. CdS-Based vdWs heterostructures exhibit super-high piezoelectricity, which have potential for the fabrication of 2D excitonic solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…All of these results are in good agreement with the published results for the same levels. [23,25,26,31,43]…”
Section: Monolayer Gan and Sihmentioning
confidence: 99%
“…[ 28 ] Moreover, Low et al found that a SiH n‐MOSFET offers a relatively better ON‐current performance than transistors made of the germanane and 2D TMD materials. [ 29 ] Furthermore, the related SiH‐based heterostructures, such as PtSe 2 /SiH, [ 30 ] InSe/SiH, [ 31 ] graphene/SiH, and fully hydrogenated hexagonal boron nitride (fhBN)/SiH, [ 32 ] have been reported. It is also found that these heterostructures exhibit main absorption of visible light.…”
Section: Introductionmentioning
confidence: 99%